Experimental Study for the Effects of Different Factors on the Sand-Carrying Capacity of Slickwater. (4th April 2023) - Peng, Huan; Li, Wenzhe; Liu, Juncheng; Peng, Junliang; Han, Huifen; Liu, Jiayi; Liu, Dan; Yang, Zhifan
Abstract : With the continuous exploration and development of unconventional oil and gas reservoirs, volume fracturing technology becomes one of the necessary measures for developing shale gas and tight sandstone gas reservoirs effectively. Volume fracturing technology usually uses slickwater and drag-reducing agent as the core of the fracturing system. The composition of the fracturing system is the main factor determining its performance. Polyacrylamide has many amide groups in its main chain, high activity, and controllable performance, often in solid powder and liquid emulsion states. Furthermore, polyacrylamide which is the water-soluble drag-reducing agent is most widely used in applying current shale gas slickwater fracturing operations. Due to the low viscosity and poor sand-carrying capacity of slickwater, proppant easily settles at the bottom of hydraulic fractures. This phenomenon influences the stimulation effect of volume fracturing. Therefore, the law of sand carrying and placement of proppant in hydraulic fractures in volume fracturing plays an essential role in determining the success of the stimulation effect of volume fracturing. Through the visualization device of proppant transport in the fracture, the settlement of proppant in the fracture was studied experimentally. And through experimental equipment, the effects of different operation pumping rates, liquid viscosity, proppant type, and proppant pumping schedule on the stimulation effect were studied. The experimental results can provide strong support for volume fracturing into well material optimization and operation parameter optimization for unconventional oil and gas reservoirs.